Endoscopic approach to recurrent inguinal hernia after previous open surgery - Doru Moga; Dragos Serban; Bogdan Geavlete; Crenguta Serboiu; Bogdan Serban; Ana Maria Dascalu; Valentin Oprea (Journal of Mind and Medical Sciences)
Background. The management of a recurrent inguinal hernia varies depending on multiple factors. In the case of recurrent inguinal hernias after open anterior repair, the laparoscopic approach is recommended. TEP and TAPP procedures are considered to have similar results. The purpose of the study is to evaluate on our sample if there are differences between primary inguinal hernia cases and recurrent hernia after laparoscopic TAPP and TEP procedures. Materials and Methods. We retrospectively reviewed the medical records of 300 patients who underwent laparoscopic inguinal hernia repairs at our hospital from March 2013 to March 2023. Results. Of the 300 patients, 39 of them (13%) had recurrent hernias after open anterior procedures. The mean age of patients with recurrent hernias was 56.82 years, compared to 50.47 years in those with primary hernias. In 27 cases we used the TAPP approach (69%), while in the remaining 12 cases the TEP approach (31%). Operative time for recurrent hernias was 72.69 minutes as opposed to 58.49 minutes for primary hernias. The percentage of peritoneal tears was higher for recurrent hernias (38%) than for primary hernias (18%). Conclusions. Surgery for inguinal hernia recurrence, is often more complex and time-consuming than for a primary hernia. However, postoperative results are favorable, with a low complication rate. Out of the two minimally invasive approach options, TAPP is our choice, especially due to the increased incidence of peritoneal tears.